Energy Address Delivery Technologies and Thermal Transformations in Food Production - Burdo O.G.; Sit M.L.; Zikov A.V.; Reznychenco D.N.; Juravleov A. A. (Problems of the Regional Energetics)
In this article, energetic and technical paradoxes in food nanotechnologies and traditional approaches to evaluation of energy recourses using are considered. Hypotheses of improvement of food production energy technologies are formulated. Classification of principles of address delivery of energy to food raw materials elements is given. We had substantiated the perspective objectives for heat-pumps installations and biphasic heat-transfer systems. The energy efficiency of new technolo-gies is compared on base of the number of energy impact. Principles of mass transfer modeling in ex-traction, dehydration and pasteurization combined processes are considered by food production exam-ple. The objectives of mathematical modeling of combined hydrodynamic and heat and mass transfer processes in modern energy technologies are set. The fuel energy conversion diagrams for drying, in-novative installations on the base of thermal siphons, heat pumps and electromagnetic energy genera-tors are represented. In this article, we illustrate how electromagnetic field, biphasic heat-transfer sys-tems and heat pumps can be effective tools for energy efficiency technologies.